Conversor estático de frequência controlado por modulação PWM senoidal - Espirito Santo, Esdras do (2019)
Frequency converters are power converters that have numerous applications, such as: transport systems, distribuited generation systems and industrial automation systems. In the latter, the frequency converter has a particular importance, as it allows the control of industrial processes that extensively use induction machines. In recent years this type of converter has also been widely used in appliances, such as: refrigerators and refrigeration systems to increase the energetic efficiency, and the lifespan of the system. In this context, this work addressed the main concepts involving frequency converters, their constituint blocks and sinusoidal PWM (Pulse- Width Modulation) techniques for producing the output signal from the inverter. Additionally, a rectfier with capacitive filter was implemented in order to attenuate the voltage ripple delivered to the DC (Direct Current) bus of the inverter, which presented a full-bridge topology. Its control was accomplished by means of SPWM (Sinusoidal Pulse-Width Modulation) technique coded in a microcontroller. The converter was able to deliver a power greater than 100 W and presented a THD (Total Harmonic Distortion) about 16,8%without the use of a filter in its output.